Design and analysis of wheelchair for usage of handicap people - Faiz Aswad, Ayop Azmi (2012)
This thesis discussed the design and analysis of wheelchair for usage of handicap people. The objectives of this thesis are to design the foldable wheelchair that can be move almost all type of surfaces and to analyze the chassis of the wheelchair. Firstly, this thesis discussed about the present market concept and materials that used for wheelchair. Later, three design concepts are suggested and the concept selection using concept screening and scoring is made. The design using Solidwork software in part by part of the wheelchair is modelled. The finite element analysis is performed by Algor software. This design analysis focused on two types of chassis materials, which are aluminium alloy and stainless steel. The maximum force of 2000N was applied to chassis model. The analysis of displacement distribution, the strain and stress contour later is discussed. The result shows that stainless steel is the best material to used for chassis of wheelchair because low in displacement distribution and stress contour compared to aluminium alloy.